Ecological Impact of Cement Dust Emissions on Vegetation Cover: A Case Study from Zliten-Libya - Khaled Harhur; Abdalla Fahej; Khaled Shahot; Ibtesam Habib (African Journal of Advanced Pure and Applied Sciences, 2026)
Cement production, while vital to infrastructure, poses environmental risks—particularly through dust emissions. This study was conducted to assess the impact of cement dust from the Ahlia Cement Factory in Zliten, Libya, on vegetation cover. Vegetation samples were collected from five sites (500, 1000, 2000, 4000, and 8000 m) south of the factory, in areas most affected by dust deposition. Vegetation cover improved with distance: plant count and species diversity peaked at 4000 m (56 plants, 10 species; ANOVA p = 0.0025, 0.0026); biomass also peaked there (211 g fresh, 166.3 g dry), though not statistically significant (p = 0.3395, 0.1270). In Hordeum murinum, leaf area increased from 78 to 1007 cm² (p = 1.84E−04), and leaf length from 8 to 14 cm (p = 0.0016), while leaf number rose slightly (7 to 9; p = 0.1333). Strong positive correlations were observed between distance and leaf length (r = 0.93), leaf number (r = 0.87), and number of plants (r = 0.79), indicating improved vegetation condition with increasing distance from the dust source.